Pure Thalamic Infarct: 8-Year Follow-Up Study in a Hospital in China - Liang, He; Sarma, Anand Karthik; Wang, Zhenxing; Mo, Ming; Lin, Jianwen; Ji, Xunming; Chen, Dong; Liu, Yi (Frontiers in Neurology, 2021)
This 8-year, single-center, retrospective study evaluated the clinical background, etiology, and follow-up results of patients with ischemic thalamic infarcts in China. Twenty-seven patients identified with acute ischemic thalamic infarcts by diffusion-weighted imaging were included. Clinical background, etiology of the Chinese ischemic stroke subclassification (CISS), and 8-year follow-up results were analyzed. All patients presented with chief complaints of limb weakness or sensory problems. Hypertension (24/27, 88.9%), diabetes (12/27, 44.4%), atrial fibrillation (1/27, 3.7%), hyperlipidemia (10/27, 37%), hyperhomocysteinemia (6/27, 22.2%), smoking history (10/27, 37%; 9/15, 60% for men; 1/12, 8.3% for women), and excessive drinking history (7/27, 25.9%; 7/15, 46.7% for men; 0 for women) were observed. CISS etiologies were as follows: 1, large artery atherosclerosis (7.14%); 23, penetrating artery disease (PAD; 85.2%); and 3, unidentified due to lack of cerebral angiography. The thalamic blood supply classifications were as follows: 23 (85.2%), inferolateral territory; 1 (3.7%), tuberothalamic territory; 2 (7.4%), combination of tuberothalamic and paramedian arteries; 1 (3.7%), combination of inferolateral and paramedian arteries; and 0, posterior choroidal arteries. During the 8-year follow-up, 3 patients died of colon cancer, multi-organ failure, or kidney failure; 7 presented with a recurrent stroke; and 10 recovered well with their risk factors under control. Ischemic thalamic infarcts are mainly classified as PAD in the CISS with hypertension as the main risk factor, and the inferolateral artery is the most vulnerable thalamic artery. Well-controlled risk factors guarantee better long-term outcomes and less stroke recurrence.